1963
DOI: 10.1086/267165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Self-Enumerative Procedure and a Personal Interview: A Validity Study

Abstract: An important mark of professional competence is a sophisticated and critical attitude toward the procedures that are used in the performance of professional functions. The best examples of social research have increasingly exhibited this attitude both in the reports of particular projects and in special research inquiries aimed primarily at testing and improving the research procedures that are in common use. It would seem that the greatest progress has been made in the development of scales of measurement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Such comparisons are rare. Cannell and Fowler (1963) found that the number of hospital stays and length of the stay were misreported more often by those who responded to later follow-ups than to earlier follow-ups. Greater discrepancies for later respondents were found on other topics (Huynh, Rupp, and Sears 2002;Stang and Jöckel 2005;Voigt et al 2005) and as predictive of sample attrition in panel studies (Bollinger andDavid 1995, 2001).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Such comparisons are rare. Cannell and Fowler (1963) found that the number of hospital stays and length of the stay were misreported more often by those who responded to later follow-ups than to earlier follow-ups. Greater discrepancies for later respondents were found on other topics (Huynh, Rupp, and Sears 2002;Stang and Jöckel 2005;Voigt et al 2005) and as predictive of sample attrition in panel studies (Bollinger andDavid 1995, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…One hypothesis about practices involving nonresponse reduction is that reluctant sample persons, successfully brought into the respondent pool through persuasive efforts, may provide data filled with measurement error (Biemer 2001;Cannell and Fowler 1963;Groves and Couper 1998). Two questions arise when this hypothesized relationship between low propensity to respond and measurement error holds.…”
Section: Introductionmentioning
confidence: 99%
“…The informal and relaxed relationship between the moderator and participants also seemed to create trust amongst participants. A number of psychologists and survey methodologists have provided evidence that high motivation levels cause respondents to put more effort in giving answers that match with their perceptions (see Dijkstra andvan der Zouwen, 1982 andCannell andFowler, 1963). On the other hand, a lack of motivation may lead to heuristics and result in inconsistent answers and satisficing (Ajzen et al, 1996;Krosnick, 1991 andTourangeau, 1984).…”
Section: Article In Pressmentioning
confidence: 99%
“…Another manifestation of panel conditioning with negative consequences is that because of participating in the panel survey, respondent may start genuinely to think or behave differently, again leading to biased estimates of change as the behaviour of panel members is no longer representative of that of the study population [73].. 12 However, panel conditioning need not always have a negative impact on measurement.…”
Section: Measurement Error Estimates Of Change Can Have Rather Diffementioning
confidence: 99%